Colleges and schools-Lyles College of Engineering-Miscellaneous 144
Members of the Math Club at Madera High School visited the School of Engineering at California State University, Fresno, (Wednesday, December 10) where they had an opportunity to see the latest developments inlaboratory equipment housed in the University's new Engineering Bilding. Dr. Irvin Kral (left), CSUF professor of Engineering, gave the 20 students a guided tour of the facilities. The students also toured the computer center and attended engineering classes during their day-long visit. They were accompanied by Robert Owen, Madera High School math teacher, and Cheryl Gollmer, Math club advisor (both seated right over). OEn said this is one several learning trips taken each year by the group.